Trends in the intensity of dense water cascading from the Arctic shelves due to ice cover reduction in the Arctic seas - F. K. Tuzov; Ф. К. Тузов (Arctic and Antarctic Research, 2021)
The article discusses the possible relationship between changes in the ice cover area of the shelf seas of the Arctic Ocean and the intensity of dense water cascading, based on calculation data obtained with the NEMO model for the period 1986–2010, with the findings issued at 5-day intervals and a spatial resolution of 1/10°. The cascading cases were calculated using an innovative method developed by the author. The work is based on the assumption that as the ice cover in the seas retreats, the formation of cooled dense water masses is intensified, which submerge and flow down the slope from the shelf to great depths. Thus, in the Arctic shelf seas, the mechanism of water densification due to cooling is added to the mechanism of water densification during ice formation, or, replaces it for certain regions. It was found that in the Barents Sea, the Laptev Sea and the Beaufort Sea, a decrease in the ice cover area causes an increase in the number of cases of cascading. However, in most of the Arctic seas, as the area of ice cover decreases, the number of cases of cascading also decreases. As a consequence, for the whole Arctic shelf area, the number of cases of cascading also decreases with decreasing ice cover. It is shown that in the Beaufort Sea the maximum number of cascading cases was observed in the winter period of 2007–2008, which was preceded by the summer minimum of the ice cover area in the Arctic Ocean. In the Barents Sea after 2000, a situation has been observed where the ice area has been decreasing to zero values, whereas the number of cascading cases has for some time (1 month approximately) remained close to high winter values. This possibly means that the cooling and densification of the waters in ice-free areas occurs due to thermal convection. Based on the calculation of the number of cases of cascading, it can be argued that the intensification of cascading due to a reduction in the ice cover is a feature of individual seas of the Arctic Ocean, those in which there is no excessive freshening ...